The reservoirs from Romania – typology and actual state. - Petre GÂȘTESCU; Victor SOROCOVSCHI (Riscuri şi Catastrofe)
The topic addressed refers to one of the solutions applied to solve the shortage of fresh water caused by global warming. In the first part of the study, the notion of lacustrine ecosystem is defined and the consequences arising from the interrelationships between abiotic and biotic factors within the ecosystem. Particular attention was paid to the comprehension of newal index for reservoirs, based on which three categories of reservoirs were identified: oligodynamic, mesodynamic and polydynamic. The clogging of reservoirs and the risks that this process can generate on the operation and durability of hydrotechnical constructions, and the components of the surrounding environment constituted the study object of the fourth chapter. Finally, based on some dominant control factors (resistance index, erosion rate, hydrochemical type, degree of mineralization), several areas with different possibilities for setting up reservoirs were identified: degree I and II favorable, acceptable, and restrictive.